Does Institutional Trust Increase Willingness to Pay More Taxes to Support the Welfare State?. Issue 1 (2nd January 2018) - Habibov, Nazim; Cheung, Alex; Auchynnikava, Alena
ABSTRACT: We evaluate the effect of institutional trust on the willingness to pay more taxes to support the welfare state. We found a positive effect of institutional trust on the willingness to pay more taxes to support the welfare state irrespective of the empirical approach used. Our instrumental variable analysis shows that causality run from institutional trust to welfare state support. A one-unit increase in institutional trust leads to a 15 percentage point increase in the willingness to pay more taxes to help the needy. Similarly, a one-unit increase in institutional trust leads to a 16 percentage point increase in the willingness to pay more taxes to support public health care and education. Consequently, institutional trust should be viewed as one of the most important mechanisms that protect the welfare state from dismantling and retrenchment. We also found a stronger effect of support for more universal programs such as public health care and education than for helping the needy.